Vitreoretinal specialists compared with residents on outcomes of primary laser retinopexy in preventing retinal detachment in 958 eyes. Issue 1 (4th February 2022) - Moussa, George; Samia-Aly, Emma; Ch'ng, Soon; Lett, Kim Son; Mitra, Arijit; Tyagi, Ajai K; Sharma, Ash; Andreatta, Walter
Abstract : Objective: Retinal tears are the most common vitreoretinal (VR) emergency and retinopexy aims to reduce the risk of rhegmatogenous retinal detachment (RRD). Currently retinal laser is a required competence by the Royal College of Ophthalmologists for residents. We report 6-month detachment rate and repeat retinopexy rate of VR specialists compared with residents. Methods and analysis: A retrospective, consecutive study of 958 eyes undergoing primary laser retinopexy (slit lamp or indirect laser) from January 2017–2020 was divided into training level by operator: specialty training (ST) 2–3, ST4–5, ST6–7 and VR specialists. Results: We report an overall 6-month RRD rate in 32/958 (3.3%) (ST2–3: 9/221 (4.1%), ST4–5: 15/373 (4.0%), ST6–7: 2/72 (2.8%) and VR specialists: 6/292 (2.1%)). We additionally report a repeat retinopexy rate of 189/958 (19.7%), (ST2–3: 44/221 (19.9%), ST4–5: 80/373 (21.4%), ST6–7: 16/72 (22.8%) and VR specialists: 49/292 (16.8%)]). Multivariable Cox survival regression analysis showed significant risk factors for developing RRD include male gender (p=0.018), high myopia (≤−6.00 Dioptres, p=0.004), ST2–3 (p=0.022) and ST4–5 (p=0.040) (relative to VR specialists) and by ST6–7, no significance was found (p=0.151). Significantly higher repeat retinopexy rates were associated with horseshoe tears (relative to round holes, p<0.001) and high myopia (p=0.026) with no difference between different training levels. Conclusion: There was a decreasing trend in RRD rate following primary retinopexy with increase in training. Although junior residents had a higher RRD rate than VR specialists, it was still favourable relative to other large case series. While there was no difference in subsequent laser retinopexy rate between training levels, the retreatment rate was associated with the type of tear and high myopia.